Analysis of Household Consumer Level Factors Affecting Beef Demand in the Source Market of the Cirebon Regency - Setiani, Desi (Jurnal Agrosci, 2023)
The purpose of this study is to ascertain the growth and demand for beef at the household consumer level in the Cirebon Regency Sumber Market, as well as the impact of broiler commercial chicken meat as a substitute item and the variables that influence the amount of beef demand at the homemaker's consumer level in the Cirebon Regency Sumber Market. The Sumber Market was chosen as the research site, with sampling as the primary factor in the decision. Sixty-eight respondents were all housewives and accidental sampling was employed using the Lemeshow formula methodology to sample the respondents. Multiple linear regression is used to analyze the data, and the SPSS 27 program is used for hypothesis testing. Traditional assumption testing includes the autocorrelation test, the normality test, and the F test. A value of F-calculated to 10,388 > F-table 2,350 indicates that the variables of beef price, consumption, chicken meat price, income, and number of family dependents (X1, X2, X3, X4, X5) together have a positive effect and significant to the demand for beef. The results showed that the demand for meat in Cirebon Regency was influenced by income (X4), which obtained a sig value of 0.01 0.05. The number of family dependents.